(untitled) (Al-Qamar, 2025)
More of a by-product of modesty and religious worship, hijab has become a cultural and fashion issue in Pakistan. In the past 20 years, this pattern has been shaped by intricate religion, media, politics and globalization cross contacts. The paper provides an analysis of the hijab phenomenon in Pakistan in a socio-cultural and fashion-based perspective by relying on historical background, literature and modern trends. This paper examines how the hijab has evolved as an item of religious attire into a debatable marker of identity, empowerment and consumer culture. This study explores how urbanization, generational changes, and media portrayals contribute to the changing perception of the hijab using a mixed-methods approach that involves a literature review, secondary survey data and content analysis on how content is represented in media. The results suggest that younger females are more likely to consider the hijab both as the religious necessity and the fashion statement which tends to follow the trends with the world of modest fashion. Pakistan has also witnessed the growth of the hijab market with business people and local brands taking advantage of the need to wear stylish yet modest clothing. At the same time, there are still stresses between conservative and liberal understandings especially in gender roles, state policies, and practices at work. The research concludes that hijab fashion in Pakistan is symptomatic of other socio-political changes, a process of negotiation of faith, modernity, and cultural expression. It further emphasizes the need to have policy interventions that acknowledge the agency of women in the stylistic decisions, and inclusiveness in education, employment, and media coverage. Keywords